2020
DOI: 10.1007/s11869-020-00866-y
|View full text |Cite
|
Sign up to set email alerts
|

Has air quality improved in Ecuador during the COVID-19 pandemic? A parametric analysis

Abstract: Many governments around the world have enforced quarantine policies to control the spread of the new coronavirus (SARS-CoV-2). These policies have had positive and negative effects on the environment. For example, the concentrations of certain harmful pollutants have decreased in some countries. In contrast, the concentrations of other pollutants have increased. This research analyzes the effect of quarantine policies on air quality in Quito, Ecuador. Using a parametric approach, it was found that NO 2 and PM2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 24 publications
1
35
0
5
Order By: Relevance
“…On July 11, 2020, Italy has introduced travel restrictions on 13 countries to combat the Covid-19 pandemic and urged its citizens to avoid international travel (Shehzad et al 2020 ). All these measures are helping governments around the world to limit the exposure from Covid-19 (Zambrano-Monserrate and Ruano 2020 ). As a consequence, transportation, businesses, and industrial shutdowns have contributed towards a significant drop in GHG emissions, i.e., in comparison with 2019, air pollutants in New York have dropped by 50%, coal use in China has decreased by 40%, and a 25% reduction in GHG emissions has been recorded in the last 3 months (Gautam 2020 ).…”
Section: Covid-19 Quarantine Policy and Impact On Air Qualitymentioning
confidence: 99%
“…On July 11, 2020, Italy has introduced travel restrictions on 13 countries to combat the Covid-19 pandemic and urged its citizens to avoid international travel (Shehzad et al 2020 ). All these measures are helping governments around the world to limit the exposure from Covid-19 (Zambrano-Monserrate and Ruano 2020 ). As a consequence, transportation, businesses, and industrial shutdowns have contributed towards a significant drop in GHG emissions, i.e., in comparison with 2019, air pollutants in New York have dropped by 50%, coal use in China has decreased by 40%, and a 25% reduction in GHG emissions has been recorded in the last 3 months (Gautam 2020 ).…”
Section: Covid-19 Quarantine Policy and Impact On Air Qualitymentioning
confidence: 99%
“…However, there was a noticeable increase of ozone pollution by 36% in Wuhan (China), 27% in Turin (Italy), 24% in Nice (France), 14% in Rome (Italy), and 2.4% in Valencia (Spain) during lockdown (Sicard et al 2020 ). In Ecuador, concentrations of NO2 and PM2.5 reduced significantly since introduction of lockdown, but O3 concentrations have grown (Zambrano-Monserrate and Ruano 2020 ). A study (Bilal et al 2020 ) found that PM2.5, O3, and NO2 have a significant relationship with cases of COVID-19 in Germany.…”
Section: Environmental and Economic Impact Of Covid-19mentioning
confidence: 99%
“…Nevertheless, in spite of the significant improvement of the air quality in many regions, it had a short-term effect, since during the gradual increase of human activity after lockdown, there was an increase of emissions up to the lockdown period ( Bherwani et al, 2020 ; Filonchyk et al, 2020a , 2020c ; Wang and Su, 2020 ). The majority of studies covered different regions of Asia and Latin America ( Broomandi et al, 2020 ; Dantas et al, 2020 ; Mahato et al, 2020 ; Siciliano et al, 2020 ; Velásquez and Lara, 2020 ; Zambrano-Monserrate and Ruano, 2020 ). Only a small number of studies examined regions in Europe, including various areas in Italy ( Bontempi et al 2020 ; Zoran et al, 2020 ) and Spain ( Baldasano et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%